2022
DOI: 10.1093/ofid/ofac375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment Outcomes of Pulmonary Mycobacterium avium-intracellulare Complex With and Without Coinfections

Abstract: Coinfections are more common in patients with cystic fibrosis and bronchiectasis. Infiltrates on imaging studies are seen more commonly in patients with coinfections, but coinfections did not affect treatment outcomes of pulmonary Mycobacterium avium complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Furthermore, the compromised airways in NTM-PD patients are more susceptible to secondary infections, and previous studies have indicated that 12% -45% of patients with Mycobacterium avium complex pulmonary disease (MAC-PD) concurrently exhibit bacterial infections [7][8][9] . Although prior investigations have consistently identified co-infection with bacterial pathogens alongside NTM acquisition or disease course, these studies have been limited by the use of sputum culture-based bacterial detection, small numbers of patients, and differences in research objectives and testing timing depending on study design [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the compromised airways in NTM-PD patients are more susceptible to secondary infections, and previous studies have indicated that 12% -45% of patients with Mycobacterium avium complex pulmonary disease (MAC-PD) concurrently exhibit bacterial infections [7][8][9] . Although prior investigations have consistently identified co-infection with bacterial pathogens alongside NTM acquisition or disease course, these studies have been limited by the use of sputum culture-based bacterial detection, small numbers of patients, and differences in research objectives and testing timing depending on study design [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%